The Influence of Service Quality on Customer Loyalty through Customer Satisfaction Mediation - Bagus Septivianto; Endi Sarwoko (Journal La Bisecoman, 2024)
One of the causes of the decline in sales at CitraLand Palu was the earthquake and tsunami of 2018 and the COVID-19 pandemic of 2019. One way to overcome this problem is to provide better quality services. In the context of the housing industry, previous research has been limited to studying the impact of service quality and customer satisfaction on loyalty. In research with campus and bank objects, different research results showed that service quality did not have a significant effect on satisfaction and loyalty. The relationship between existing variables shows that the influence of service quality on customer loyalty is tentatively unlimited, and there are still differences in research results. It needs to be tested in further research and is a gap for research in the context of housing objects. This research examines the influence of service quality in residential facilities on customer satisfaction. This study also examines customer satisfaction as a mediating factor in creating customer loyalty. Based on the type of data obtained, the author uses quantitative methods; a questionnaire is used as a tool for data collection. Data analysis in research uses path analysis, assisted by SPSS software.